Purification of the human apical conjugate export pump MRP2 - Hagmann, Wolfgang; König, Jörg; Zentgraf, Hanswalter; Keppler, Dietrich (EJB, 2001)
The multidrug resistance protein MRP2 (ABCC2) acts as an ATP-dependent conjugate export pump in apical membranes of polarized cells and confers multidrug resistance. Purified MRP2 is essential for the detailed functional characterization of this member of the family of ATP-binding cassette (ABC) transporter proteins. In human embryonic kidney cells (HEK293), we have permanently expressed MRP2 containing an additional C-terminal (His)6-tag. Immunoblot and immunofluorescence analyses detected the MRP2-(His)6 overexpressing clones. Isolated membrane vesicles from the MRP2-(His)6-expressing cells were active in ATP-dependent transport of the glutathione S-conjugate leukotriene C4 and were photoaffinity-labelled with 8-azido-[α-32P]ATP. MRP2-(His)6 was solubilized from membranes of MRP2-(His)6-cells and purified to homogeneity in a three-step procedure using immobilized metal affinity chromatography, desalting, and immunoaffinity chromatography. The identity of the pure MRP2-(His)6 was verified by MS analysis of tryptic peptides. The purified MRP2-(His)6 glycoprotein was reconstituted into proteoliposomes and showed functional activity as ATPase in a protein-dependent manner with a Km for ATP of 2.1 mm and a Vmax of 25 nmol ADP·mg MRP2−1·min−1. This ATPase activity was substrate-stimulated by oxidized and reduced glutathione and by S-decyl-glutathione. Future studies using pure MRP2 reconstituted in proteoliposomes should allow further insight into the molecular parameters contributing to MRP2 transport function and to define its intracellular partners for transport and multidrug resistance.
First published: 25 December 2001
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 23.02.2021